Effects of Argument Quality, Need for Cognition and Issue Involvement to The Attitude Toward a Message Given Through Persuasive Communication - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The present study was an experimental study. The goal of the study was to find out the effects of the quality of an argument, need for cognition (NC) and the degree of issue involvement, altogether in determining the attitude toward a message given through persuasive communication. The subjects were 80 students from 121 fresh (entry) students of the Faculty of Psychology, Gadjah Mada University, year 1995/1996. The subject was then randomly assigned to four manipulation groups. Each group was given one of the four types of manipulation, which were combinations of the quality of the arguments (strong or weak) and the degree of issue involvement (high or low). After the manipulation, the subjects were given an attitude scale measuring their favorableness toward the issue. The data was analyzed with three-ways factorial ANOVA. The results supported the hypothesis of the study. It can be concluded that when argument was strong, the higher motivation (that is, the higher NC and the involvement) to process the message, the stronger the favorableness toward the issue. On the other hand, when the argument was weak, higher motivation resulted in weaker favorableness. This study also found that the NC as a motivating factor had stronger influence rather than issue involvement.